Comparing the midterm outcome of single incision vaginal mesh and transobturator vaginal mesh in treating severe pelvic organ prolapse - Tsai-Hwa Yang; Ling-ying Wu; Fei-Chi Chuang; Fu-Tsai Kung; Kuan-Hui Huang (Elsevier, 2017)
Objective: The aim of this study is to compare perioperative parameters and midterm clinical outcomes using two different mesh kits: transobturator vaginal mesh (TVM) (both Perigee and Apogee), versus single incision vaginal mesh (SIM) (combined Elevate anterior/apical system and Elevate posterior/apical system) in treating severe pelvic organ prolapse (POP). Materials and Methods: This is a retrospective cohort study. During 2008 and 2013, those women with severe POP [POP quantification system (POP-Q), Stage III and Stage IV], who received either TVM or SIM operation, were enrolled for cohort comparison. There were 111 patients in the TVM group, and 136 in the SIM group. Those with an incomplete POP-Q record, or who did not complete postoperative urodynamic study were excluded. Perioperative characteristics and outcomes, postoperative urinary symptoms, urodynamic parameters, prolapse recurrence (defined as the leading edge > 0 using the POP-Q system), and mesh extrusion rate were compared. Results: There were no differences in the operation time, blood loss, hospital stay, and the postoperative visual analog scale for pain. Urodynamic studies showed improvement in bladder outlet obstruction in both groups. The postoperative stress urinary incontinence was significantly higher in the SIM group. The recurrence of prolapse was comparable between the two groups at a median follow-up of 2 years. The mesh extrusion rate was significantly lower in the SIM group. Conclusion: At an average of 2 years of follow-up, the mesh extrusion rate was lower in the SIM group than in the TVM group, but there was no difference in postoperative visual analog scale for pain. The postoperative stress urinary incontinence was higher in the SIM group.